A Neoclassical Measure of Profit. - Scapens, Robert W. (The Accounting Review, 1978)
This article seeks to develop the concept of profit used in the microeconomic theory of the firm and to examine its potential as an accounting measure. Using a simple economic model, it is demonstrated that profit maximization can be the short-run analogue of long-run wealth maximization. Economic profit is compared with certain of the existing proposals for financial reporting and similar income measures are observed, Certain differences between some existing proposals are traced to a fundamental difference of opinion about the nature of a business enterprise. It is concluded that economic profit appears to have potential as an accounting measure. However, it is pointed out that empirical research will ultimately be required to determine the usefulness of the measure to financial statement users.